Pelatihan Penyusunan RPP Terbaru untuk Meningkatkan Kompetensi Pedagogik Guru di MTS-MA darul Azhar - Fuji Pratami; Irma Suryani Siregar (Jurnal Abdimas Adpi Sosial dan Humaniora, 2022)
This service is carried out because the MTs-MA Darul Azhar teacher's understanding has not been maximized to prepare the Latest RPP in accordance with the Minister of Education and Culture's Circular Letter Number 14 of 2019. The purpose of this service is to socialize and provide training on making the Latest RPP to MTs-MA Darul Azhar teachers. The method used to solve problems in this community service program is service learning. The results of this service are (1) the MTs-MA Darul Azhar teacher has been given trick material for compiling the Latest RPP; (2) MTs-MA Darul Azhar teachers have been able to prepare the Latest RPP properly and according to components. There were several things that were found during the socialization and training for the preparation of the Latest RPP, as follows: (1) The latest RPP compiled by the participants of the socialization still exceeded one page; (2) the preparation of learning objectives that have not followed the Audience, Behavior, Condition, and Degree (ABCD) format; (3) participants still have difficulty choosing the right learning model with the material and characteristics of students; (4) several student learning activities that are in accordance with the syntax of the selected learning model; and (5) participants were confused in determining the assessment related to the cognitive, psychomotor and affective domains. The findings during the socialization and training have been improved, so that participants understand and are able to prepare the Latest RPP well. This socialization and training is expected to improve the pedagogic abilities of teachers as participants. Hopefully in the future the pedagogic competence of teachers in compiling the latest RPP will improve.